Impacts of the 2017 Brazilian National Primary Care Policy on public primary health care in Rio de Janeiro, Brazil - Fabricio Loureiro Garcia; Mariana Socal (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2022)
In 2017, in a scenario of financial restrictions caused by an economic crisis in Brazil, a new primary health care policy promoted changes in the way different primary health care models were prioritized and implemented, with possible negative effects on the access to primary health care. This study aims to investigate if the 2017 Brazilian National Primary Care Policy (PNAB) negatively affected the primary care organization based on the Family Health Strategy (FHS) model and on the access to public primary care services in the city of Rio de Janeiro. The annual averages and the pre- and post-2017 averages of 15 variables were analyzed to identify possible trend breaks in 2017. A Bayesian structural time series model was used to determine the differences between actual and predicted post-2017 averages of each variable. The data were obtained via the Brazilian Health Informatics Department (DATASUS), the Department of Informatics of the Brazilian Unified National Health System. The annual average of family health teams was 1,179.9 teams, in 2017, and 788.8 teams in 2020, while the annual average of equivalent family health teams was 163.6, in 2017, and 125.4, in 2020. The actual post-2017 average of 989.3 family health teams (p = 0.004) was 16.7% lower than the predicted post-2017 average of 1,187.4 teams. In total, 62.6% and 40.5% of the population in Rio de Janeiro were covered by the FHS in 2017, and 2020, respectively. The provision of public primary care services decreased after 2017. Results show a deterioration of the FHS in Rio de Janeiro after 2017 and no increase in the traditional primary care model. Access to public primary care services reduced in the same period.